THE FOOTBALL, BASKETBALL AND VOLLEYBALL PLAYERS ANTROHOMETRIC CHARACTERISTICS - Arif Bronja-prof VSCG; Admira Koničanin (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
45 examiners (samples) whish are active in sport and in already mentioued sport 's disciplines (football, basketball, volleyball) devided into three groups are included into this research. The aim: the reserarch is antropologic ande it is firstly pointed to the exemination of the difference between the anthropological characteristis of the football, basketball and volleyball players from bar's sports clubs. The hypotheses that the statistic importaut differences among football, basketball and volleyball players exist are determined by the research